The Effect of Changes in VAT Rates and Company Risks on Tax Avoidance in Coal Mining Companies - Meita, Iren; Nurdiniah, Dade (IJBLE Scientific Publications Community Inc., 2024)
One of the largest contributors to state income is mining companies, where in 2019 mining companies contributed tax revenues of IDR 33.43 trillion. Based on Law No. 11 of 2020 concerning Job Creation which amends the VAT Law Article 4A paragraph (2), Coal was previously not subject to VAT, and in 2022 the VAT rate will change to 11%, which was previously 10%, so from this explanation the aim of this research is to determine the relationship between changes in VAT rates on tax avoidance and the relationship between company risk and tax avoidance. The research object used is from the Indonesian Stock Exchange for Coal Mining Companies in Indonesia from the year corresponding to the start of VAT imposition and changes in rates, namely 2021-2023. Data were analyzed using multiple regression analysis, and to determine the sample using purposive sampling technique. From the results of the hypothesis test, it was found that there is no significant relationship between changes in VAT rates and tax avoidance, and there is a significant relationship between company risk and tax avoidance.